Human health risk assessment of airborne metals to a potentially exposed community : a screening exercise - Oosthuizen, M.A.; Matooane, M.; Phala, N.; Wright, C.Y. (Clean Air Journal = Tydskrif vir Skoon Lug, 2015)
Exposure to high concentrations of inhalable particulate matter (PM) is a known human health risk, depending on the chemical composition of the PM inhaled. Mogale City (Gauteng) is known for having several sources of airborne PM, however, less is known about the metals in the airborne PM. The aim of this study was to determine the metals in measured PM at Kagiso, Mogale City. An independent PM10 monitor was installed at the municipality's existing monitoring site. This monitor continuously monitored PM10 between 23 August and 9 October 2013 and simultaneously sampled particles below 20 µm in diameter onto a glass fibre filter. This filter was replaced once towards the middle of the monitoring period. These two filters were chemically analysed to determine their metal content (30 metals) by the South African Bureau of Standards accredited laboratory at the Council for Scientific and Industrial Research by means of Inductively Coupled Plasma Spectroscopy (ICPS) based on the US EPA Method IO-3.1. To provide an estimate of possible health risk, the metal concentrations were used in a screening US-EPA human health risk assessment (HHRA). Since the analysed metals were reportedly below the detection limit, three hypothetical exposure scenarios (S) based on US-EPA recommendations were created for the HHRA. In S1, concentrations were considered to be the same as the detection limit for each metal; S2 assumed concentrations to be 50% of the detection limit; and S3 put concentrations at 10% of the detection limit. Potential risks (should pollution worsen) of developing respiratory and neurological effects were identified depending on the hypothetical scenarios. Continuous long-term monitoring and chemical characterisation are necessary to confirm these preliminary findings.